Prevalence of the BRCA1 c.68_69delAG (BIC: 185delAG) mutation in women with breast cancer from north-central Poland and a review of the literature on other regions of the country - Hartwig, Martyna; Janiszewska, Hanna; Bąk, Aneta; Pilarska, Maria; Heise, Marta; Junkiert-Czarnecka, Anna; Laskowski, Ryszard; Haus, Olga (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Germline mutations in BRCA tumor suppressor genes are strongly associated with breast and ovarian cancer. The lifetime risk of these cancers in women with BRCA1 mutation is 84% and 27%, respectively. Studies on the prevalence of BRCA1 c.68_69delAG congenital mutation, the most frequent in Ashkenazi Jews, among women with breast cancer from north-central Poland and review of the literature on other regions of the country. Evaluation of the c.68_69delAG association with breast cancer risk, with respect to women’s age at diagnosis and family history of cancer. Material and methods : 252 women with breast cancer, without any of the mutations c.5266dupC, c.181T>G, or c.4034delA, regardless of histological type and family history of cancer. The mutation was detected using allele-specific oligonucleotide polymerase chain reaction (ASO-PCR) assay and confirmed by sequence analysis. Results: The c.68_69delAG mutation was disclosed in one out of the 252 women (0.4%), who had been diagnosed with breast cancer at age 43. Family investigations revealed the presence of c.68_69delAG also in the patient’s mother, diagnosed with breast cancer at age 68. Sequence analysis confirmed the heterozygous status of the mutation, and family investigation its hereditary character. In the group of families with breast cancer history 1.4% frequency of c.68_69delAG was shown. Conclusions : Among families with breast cancer aggregation, originating from north-central Poland, c.68_69delAG is a rare BRCA1 alteration, similarly to other central regions of the country, investigated by other authors. However, in northern, north-western and south-western parts of Poland, it occurs 2–4 times more frequently than in our region.